Anxiety, Anger and Depression Amongst Low-Income Earners in Southwestern Uganda During the COVID-19 Total Lockdown - Archibong, Victor; Usman, Ibe Michael; Keneth Iceland, Kasozi; Osamudiamwen, Eric Aigbogun Jr.; Josiah, Iﬁe; Monima, Ann Lemuel; Ssebuufu, Robinson; Chekwech, Gaudencia; Terkimbi, Swase Dominic; Owoisinke, Okon; Mbiydzenyuy, Ngala Elvis; Adeoye, Azeez; et al. (Kabale University, 2023)
Background: Low-income earners are particularly vulnerable to mental health, consequence of the coronavirus disease 2019 (COVID-19) lockdown restrictions, due to a temporary or permanent loss of income and livelihood, coupled with government-enforced measures of social distancing. This study evaluates the mental health status among low-income earners in southwestern Uganda during the ﬁrst total COVID-19 lockdown in Uganda. Methods: A cross-sectional descriptive study was undertaken amongst earners whose income falls below the poverty threshold. Two hundred and ﬁfty-three (n = 253) male and female low-income earners between the ages of 18 and 60 years of age were recruited to the study. Modiﬁed generalized anxiety disorder (GAD-7), Spielberger’s State-Trait Anger Expression Inventory-2 (STAXI-2), and Beck Depression Inventory (BDI) tools as appropriate were used to assess anxiety, anger, and depression respectively among our respondents. Results: Severe anxiety (68.8%) followed by moderate depression (60.5%) and moderate anger (56.9%) were the most common mental health challenges experienced by low-income earners in Bushenyi district. Awareness of mental healthcare increased with the age of respondents in both males and females. A linear relationship was observed with age and depression (r = 0.154, P = 0.014) while positive correlations were observed between anxiety and anger (r = 0.254, P < 0.001); anxiety and depression (r = 0.153, P = 0.015) and anger and depression (r = 0.153, P = 0.015). Conclusion: The study shows the importance of mental health awareness in low resource settings during the current COVID-19 pandemic. Females were identiﬁed as persons at risk to mental depression, while anger was highest amongst young males. Keywords: COVID-19 response, Africa, Socio-economic impacts, Psychosocial, Hunger, Women.